2001
DOI: 10.1002/ajim.1059
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms among crab processing workers in Alaska: Epidemiological and environmental assessment*

Abstract: Both personal and process-related factors appear to affect the development of respiratory symptoms in crab processing workers. In this study, crab specific IgE was not detected in most of the workers with new symptoms. Published 2001 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 15 publications
3
26
0
Order By: Relevance
“…Most studies that have addressed occupational exposure to seafood antigens have mainly concentrated on crustacean (crab and shrimp) and very scantily on fish (salmon, whiff megrim and hake) [10,14,15,16,17,18,19,20]. Either pooled human sera from patients known to be allergic to the particular seafood agent or monoclonal antibodies to a major antigen previously identified were used for the detection of antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies that have addressed occupational exposure to seafood antigens have mainly concentrated on crustacean (crab and shrimp) and very scantily on fish (salmon, whiff megrim and hake) [10,14,15,16,17,18,19,20]. Either pooled human sera from patients known to be allergic to the particular seafood agent or monoclonal antibodies to a major antigen previously identified were used for the detection of antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Often rural and remote plants can result in affected workers remaining at their jobs, making it difficult for them to obtain a specific diagnosis and access to workers' compensation. 3 Previous studies have shown the primary source of antigen exposure in seafood processing to be the inhalation of aerosolized proteins ranging in molecular weight from 10 to 70 kd. 7 In the crab industry these aerosols often contain primarily crab exoskeleton, muscle protein, gills, and internal organs with lesser amounts of background material, such as cellulose, synthetic fibers, and inorganic particles.…”
mentioning
confidence: 99%
“…2 The cleaning, steaming, washing, sawing, cracking, and crushing of snow crabs within these plants can routinely expose many workers to crab proteins in the form of dust, steam, vapor, and crab meat (CM). 3 These conditions place the plants' usually seasonally employed laborers at risk for occupational IgE-mediated allergic disease. [4][5][6] Respiratory illnesses in these workers negatively affect their quality of life and, for those forced to give up their jobs, imposes economic burdens on them and their families because of limited employment alternatives and infrequent access to health specialty services.…”
mentioning
confidence: 99%
“…Several studies report a high incident of occupational asthma in workers processing snow crab (Chionoecetes opilio) and king crab (Paralithodes camtschaticus), but other symptoms as rhinitis, conjunctivitis, and skin rash are also registered (Orford and Wilson, 1985;Cartier et al, 1986;Ortega et al, 2001;Howse et al, 2006;Gautrin et al, 2009). Although a majority of the literature point to an IgE-mediated mechanism for the development of respiratory disease among crab processing workers, there are reports that fail to show a clear correlation between crab specific IgE and new incidents of asthma-like and bronchitis cases (Ortega et al, 2001). Workers processing saltwater bony fish (sardine (Sardinops sagax) and anchovy (Engraulis capensis)) also appear to be at increased risk for developing work-related upper and lower allergic respiratory outcomes (Jeebhay et al, 2008).…”
Section: Introductionmentioning
confidence: 99%